2008
DOI: 10.1371/journal.pone.0003640
|View full text |Cite
|
Sign up to set email alerts
|

HIV Incidence in Rural South Africa: Comparison of Estimates from Longitudinal Surveillance and Cross-Sectional cBED Assay Testing

Abstract: BackgroundThe BED IgG-Capture Enzyme Immunoassay (cBED assay), a test of recent HIV infection, has been used to estimate HIV incidence in cross-sectional HIV surveys. However, there has been concern that the assay overestimates HIV incidence to an unknown extent because it falsely classifies some individuals with non-recent HIV infections as recently infected. We used data from a longitudinal HIV surveillance in rural South Africa to measure the fraction of people with non-recent HIV infection who are falsely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 31 publications
3
73
1
Order By: Relevance
“…The addition of validated TRI to cross-sectional HIV surveys, 13 such as the DHS, would allow better prioritization for prevention of HIV acquisition than is currently possible. TRI are easy to apply.…”
Section: Figmentioning
confidence: 99%
See 4 more Smart Citations
“…The addition of validated TRI to cross-sectional HIV surveys, 13 such as the DHS, would allow better prioritization for prevention of HIV acquisition than is currently possible. TRI are easy to apply.…”
Section: Figmentioning
confidence: 99%
“…In a systematic review, 16 we identified 39 published studies (up to March 2009) that estimated HIV incidence based on information obtained by applying the BED assay, the particular TRI used in the present study. Past applications of the BED assay included national and subnational HIV surveys of general populations in subSaharan Africa, 13,17,18 demonstrating that it is indeed feasible to add TRI to large-scale surveys in the region. Further studies are needed to estimate the cost-effectiveness of routinely adding TRI to HIV surveys in sub-Saharan Africa.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations